Cost-Benefit Analysis of Seismic Mitigation Measures for Wine Barrel Stacks. Issue 1 (February 2018) - Jaimes, Miguel A.; Candia, Gabriel; Favier, Philomène
This study conducts a cost-benefit analysis of alternative seismic risk mitigation methods for wine barrel stacks. The Chilean wine industry is presented as an illustrative case study in which performance metrics, such as the expected annual loss (EAL) and benefit-cost ratios, are computed for wineries at different locations. By computing seismic risk within a consistent framework, this study shows the value of cost-benefit simulations for defining the best mitigation strategies and allocating economic resources. Likewise, this approach helps communicate information to decision makers because it is presented in a simple and transparent way, even if they are not familiar with formal risk studies. For three-level wine barrel stacks, it was observed that the Cradle Extender ® (MS1) prevents a large number of barrel collapses and provides the highest benefit-cost ratio. On the other hand, for six-level wine barrel stacks, the prestressed cable (MS2) is more effective than MS1 as it prevents the barrel stack from overturning. No significant loss reduction is apparent in four- and five-level wine barrel stacks with the use of mitigation strategies; indeed, the mitigation strategies could generate greater losses and, therefore, other alternatives must be proposed.